PRESCRIPTION PATTERN MONITORING OF NON-STEROIDAL ANTIINFLAMMATORY DRUGS IN URBAN HEALTH CENTRE IN TALEGAON: A RETROSPECTIVE STUDY - NIDHI MAHESHWARI; RANJIT J. WAGH; APARNA S CHINCHOLKAR; MANJEETA GUPTA (International Journal of Pharma and Bio Sciences, 2015)
Non Steroidal Anti Inflammatory Drugs (NSAIDs) are commonly prescribed agents for treating pain and inflammation, over and inappropriate use of which leads to significant clinical problems. The study aimed to know the rationality of their usage. A retrospective audit of 532 prescriptions in year 2012 at the outpatient department of Urban Health Centre attached to a medical college was done. Out of those 263 (49.4%) contained NSAIDs. 44% of these 263 prescriptions reported Upper Respiratory Tract Infection (URTI) as the most commonly diagnosed clinical condition, followed by localised pain, body-ache and backache. Paracetamol and diclofenac were commonly prescribed drugs. The average number of drugs per encounter was 2.56 and the average number of NSAIDs per prescription was 1.29. 7.6% patients received ibuprofen-paracetamol (Ibu-para) which is an irrational combination.More than half of the NSAIDs were prescribed by proprietary names. No adverse drug reaction or side effects were recorded. Most of the prescriptions at the health care centre were in accordance with the WHO guidelines and recommendation for diseases. Prescription behaviors influenced as per availability of drugs.